Frugivoria e dispersão de sementes pelo Jabuti-Piranga Chelonoidis carbonaria - Rodrigues, Laís Lautenschlager [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Seed dispersion plays a key role in plant reproduction and the failure in this process can jeopardize the establishment and survival of plant species. Several studies addressing the dispersal of seeds by birds and mammals, while saurochory - dispersion by reptiles - receives relatively little attention. This study aims to understand if red-footed tortoises (Chelonoidis carbonaria) can be considered as potential seed dispersers. So, native or exotic species of fruits was offered, with variations in their seed sizes, noting the ability of individuals to feed themselves and swallow; we recorded the retention time of the seeds in the digestive system of individuals and after defecation, a seed germination test occurred in order to verify if the passage through the digestive system of tortoises changes the germination and/or affect the seeds' viability. A total of 40 species of seeds were offered to individuals, obtaining a maximum of 23mm diameter swallowed. In the retention time test, with Jacaratia spinosa species was obtained 3-14 days (mean 8 days); Genipa americana, 6-28 days (mean 17 days), Syagrus romanzoffiana and Euterpe edulis approximately 5-17 days (mean 10 days) of retention. The germination rate varied between species, so in J. spinosa and S. romanzoffiana was verified positive influences, i.e. defecated seeds germinated faster than those grown without treatment (control). Subsequently, the tetrazolium test was performed with the remaining seeds and it was observed that in all cases the viability rate was higher with defecated species than the control; was not performed tetrazolium test with E. edulis because all defecated seeds had its embryo damaged and/or rotted. We conclude that Jabuti-Piranga (Chelonoidis carbonaria), being able to swallow seeds and positively influencing the germination of seeds, can be used as ecologic substitutes in catering areas where there is a lack of large dispersers, due to the consequences of...

A dispersão de sementes representa um papel fundamental na reprodução das plantas, sendo que a falha neste processo pode comprometer o estabelecimento e sobrevivência das espécies vegetais. Diversos estudos abordam a dispersão de sementes por aves e mamíferos, enquanto que a saurocoria - dispersão por répteis - recebe relativa pouca atenção. O presente estudo visou compreender se os Jabutis-Piranga (Chelonoidis carbonaria) podem ser considerados potenciais dispersores de sementes. Sendo assim, foram oferecidos frutos de espécies nativas e exóticas, com variações nos tamanhos de sementes e observado a capacidade dos indivíduos de alimentarem-se e engolirem; foi contabilizado o tempo de retenção das sementes no sistema digestório dos indivíduos e após a defecação, realizado o teste de germinação das sementes, no intuito de verificar se a passagem pelo sistema digestório dos jabutis poderia alterar a capacidade de germinação e/ou afetar a viabilidade das sementes. Um total de 40 espécies de sementes foram oferecidas aos indivíduos, obtendo um limite máximo de 23 mm de diâmetro engolido. Para o tempo de retenção foram utilizadas as espécies Jacaratia spinosa, obtendo 3-14 dias (média: 8 dias); Genipa americana, de 6-28 dias (média: 17 dias), Syagrus romanzoffiana e Euterpe edulis, com aproximadamente de 5-17 dias (média: 10 dias) de retenção. A taxa de germinação variou entre as espécies, sendo que em S. romanzoffiana e J. spinosa houve influências positivas, ou seja, sementes defecadas germinaram mais rapidamente do que as plantadas sem nenhum tratamento (controle). Posteriormente, o teste de tetrazólio foi realizado com as sementes remanescentes à germinação e observou-se que em todos os casos a taxa de viabilidade foi maior com as espécies defecadas do que as controle; não foi realizado teste de tetrazólio com sementes de E. edulis pois todas as sementes defecadas estavam com o embrião...
Keywords: Sementes; Frugivoria; Jabutis; Plantas - Reprodução; Germinação; Sementes - Viabilidade; Sementes - Disseminação; Ecologia vegetal